2004
DOI: 10.1186/bcr932
|View full text |Cite
|
Sign up to set email alerts
|

The changing global patterns of female breast cancer incidence and mortality

Abstract: Usage Guidelines Please refer to usage guidelines at http://researchonline.lshtm.ac.uk/policies.html or alternatively contact researchonline@lshtm.ac.uk.Available under license: http://creativecommons.org/licenses/by/2.5/ 229Available online http://breast-cancer-research.com/content/6/6/229 IntroductionCancer of the breast in women is a major health burden worldwide. It is the most common cause of cancer among women in both high-resource and low-resource settings, and is responsible for over one million of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
599
4
24

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 789 publications
(636 citation statements)
references
References 75 publications
9
599
4
24
Order By: Relevance
“…Breast cancer is the most frequently diagnosed cancer in Asian women (Miller et al, 1996;D'Souza et al, 2013). Although South Asian women in their home countries are reported to have a low incidence of breast cancer, changing global patterns indicate growing Insiya B Poonawalla 1 , Sharad Goyal 2 , Naveen Mehrotra 3 , Marlyn Allicock 4,5 , Bijal A Balasubramanian 1,5 * trends similar to other developed countries (Bray et al, 2004;Althuis et al, 2005;Ghumare and Cunningham, 2007). Migrant studies have clearly shown that as the number of years lived in developed countries such as the US increases, the risk of breast cancer also increases (Kaur, 2000;National Cancer Institute, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Breast cancer is the most frequently diagnosed cancer in Asian women (Miller et al, 1996;D'Souza et al, 2013). Although South Asian women in their home countries are reported to have a low incidence of breast cancer, changing global patterns indicate growing Insiya B Poonawalla 1 , Sharad Goyal 2 , Naveen Mehrotra 3 , Marlyn Allicock 4,5 , Bijal A Balasubramanian 1,5 * trends similar to other developed countries (Bray et al, 2004;Althuis et al, 2005;Ghumare and Cunningham, 2007). Migrant studies have clearly shown that as the number of years lived in developed countries such as the US increases, the risk of breast cancer also increases (Kaur, 2000;National Cancer Institute, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Breast cancer is the most common malignancy in women, as about a million new cases of this cancer are diagnosed world-wide each year, and 375,000 women die from it (1). Although early detection through screening mammography has increased the proportion of in situ and early stage breast cancers that have excellent prognosis, mortality rates from recurrent and late stage breast cancers have not declined significantly (2).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer incidence has been generally rising over the last 50 years (Parkin and Fernandez, 2006) with rapid increases observed particularly in developing countries (Bray et al, 2004), including those in the Middle-East (El Saghir et al, 2007). Interestingly, developing countries show a higher incidence of breast cancer in urban compared to rural areas (Dey et al, 2010).…”
Section: Edcs and Breast Cancermentioning
confidence: 99%